Analisis Kinerja Keuangan Perusahaan dengan Menggunakan Du Pont System - Shifa Amalia Rahmani; Hasbi Assidiki Mauluddi (Journal of Applied Islamic Economics and Finance, 2020)
The development and growth of Islamic banks in Indonesia is very rapid. PT. Bank Muamalat Indonesia as a pioneer of Islamic banks in Indonesia is increasingly in the spotlight of various parties. The resulting performance is always an interesting thing to study further. The company's financial performance can be seen from the ratio of profitability, profitability, solvency and the activities it generates. One calculation tool for profitability is Return On Investment. If the Return On Investment in a company increases, then it shows the more efficient the company is in utilizing its assets, the greater the benefits that can be achieved by the company so that the company's value is also better and more efficient in generating profits. The calculation tool for calculating Return On Investment is a du pont system, where the du pont system focuses on the results of the calculation of net profit margins, total assets turn over and return on investment. The purpose of this study was to determine the financial performance of PT. Bank Muamalat Indonesia for the period 2008-2017 with the studied variables are Net Profit Margin, Total Asset Turn Over and Return On Investment. The conclusion in this study is the net profit margin, total assets turnover and return on investment produced has a fluctuating value.